The Effect Of Parents' Social Economic Status and Learning Motivation On Economic Learning Achievement Of Students Of Class X Sma Negeri 1 Arse Academic Year 2017/2018 - Yesika Theresia Harahap (Outline Journal of Education, 2022)
The problem in this research is the low of student economic learning Outcomes.This study aims to determine the influence of socio economics of parents and student achievement, intereset to learning motivation with student achievement and determine the influence of teacher creativity and learning motivation with student achievement X SMA Negeri 1 Arse school Year2017/2018.This research was conducted in senior high school 1 Arse in Simangambat street, North Tapanuli. There is all of the class X numbered 112 students as population in this research. The sample in this study using 56 people. Instrument that used to collecting data is questionnaire with using likert scale that firstly tested the validity and reliability of the questionnaire before conducting research. The analysis used in this research is testing variable partially performed by t test while testing for both variables togetger with F test.Based on the analysis and discussion of this study concluded that (1) There is a positive significant influence between socio economics of parents and student achievement with tcount (4,407) > ttable ( 2,004). (2) There is apositive significant influence between learning motivation with tcount (4,962) > ttable (2,004). (3) There is a significant influence between socio economics of parent and learning motivation together with Fcount> Ftable namely ( 97,108 > 3,17).Based on the analysis, the conclusions from this study is there a positive and significant influence between teacher creativity and learning motivation with student achievement in class X SMA Negeri 1 Arse and hipotesis in this research can accepted